High strength pipe resistant to aluminum sulfate corrosion and method of manufacturing same
Patent Information
- Application Number
- JP2024543320
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-01-26
- Filing Date
- 2023-01-18
- Publication Date
- 2025-02-04
AI Technical Summary
を発揮するために、本開示の耐食層において、C元素の質量百分率は、0
Smart Images

Figure 2025503778000001_ABST
Abstract
Description
[Technical field]
[0001] FIELD OF THE DISCLOSURE This disclosure relates to tubes and methods of manufacture, and more particularly to high strength tubes that are resistant to aluminum sulfate corrosion and methods of manufacture. [Background technology]
[0002] At present, it is usually necessary to add aluminum sulfate before the mixing tank and thickening tank for flocculation in the water supply station or water supply pipeline network. Therefore, in order to ensure the service life of the pipeline and equipment, good aluminum sulfate corrosion resistance is required when manufacturing pipes or equipment such as aluminum sulfate mixing tank, thickening tank, connecting pipe for tank body, and pipe for adding aluminum sulfate.
[0003] In the prior art, UPVC and CPVC materials are commonly used to produce the above-mentioned pipelines and equipment for transporting aluminum sulfate, in order to prevent these equipment and pipelines from corroding. However, the practical application of UPVC and CPVC materials is not ideal, as they face problems such as being difficult to process, having a large expansion coefficient, low strength, and being prone to softening and deformation during use.
[0004] At present, some researchers are considering using carbon steel to prepare the above equipment and pipelines. However, the carbon steel inner walls of the mixing tank, the thickening tank, the connecting pipe for the tank body, and the pipe for adding aluminum sulfate, which are made of carbon steel material, will inevitably be corroded by aluminum sulfate during actual use. This will not only cause water pollution, but also very likely lead to pipe leakage and pipe bursting.
[0005] In addition, some researchers have tried to use 300 series austenitic stainless steel to prepare the above equipment and pipelines. However, 300 series austenitic stainless steel has lower structural strength than carbon steel, thus requiring a larger thickness, thus increasing the amount of material used. In addition, 300 series austenitic stainless steel is difficult to weld and machine. In addition, 300 series stainless steel itself contains a relatively large amount of precious metal elements such as Cr and Ni, so the cost of using pure stainless steel in its production, manufacturing and installation process is relatively high.
[0006] Therefore, in view of the deficiencies and defects existing in the prior art mentioned above, it is desirable to obtain a new pipe in which a reasonable design is adopted so that an aluminum sulfate corrosion resistant layer can be formed on the surface of the carbon steel of the base layer. The finished pipe is resistant to aluminum sulfate corrosion, has good mechanical properties and high economic efficiency, and has great economic and social benefits. Summary of the Invention [Problem to be solved by the invention]
[0007] One of the objectives of the present disclosure is to provide a pipe in which a rational design is adopted so that an aluminum sulfate corrosion resistant layer can be formed on the surface of the carbon steel of the base layer. The finished pipe is resistant to aluminum sulfate corrosion, has good mechanical properties and high economic efficiency, and has great economic and social benefits. [Means for solving the problem]
[0008] The pipe of the present disclosure makes it possible to solve the inherent weaknesses of 300 series stainless steel or carbon steel used in water stations in environments containing aluminum sulfate corrosive media. The pipe can be effectively used in pipelines and equipment used in water stations in environments containing aluminum sulfate media, greatly improving the applicability, safety, and durability of these pipelines and equipment while avoiding secondary contamination of water quality.
[0009] In order to achieve the above object, the present invention provides a pipe having a corrosion resistant layer and a base layer in the thickness direction, the corrosion resistant layer being located at least on the inner wall of the pipe, the corrosion resistant layer further comprising, in addition to Fe and inevitable impurities, the following chemical elements in wt%: 0 <C≦0.08%; Si: 0.3-0.6%; Mn: 0.5-2.0%; Ni: 11.00~13.00%; Cr: 16.50~18.00%; Mo: 2.00-3.00%; N: 0.02-0.15%; and Cu: 0.01-0.30% where Cr, Mo, N, and Cu satisfy the following inequalities: Cr+3.3×Mo+16×N+10×Cu≧26.0% Fill the tube.
[0010] Preferably, the corrosion resistant layer comprises the following chemical elements in wt%: 0 <C≦0.08%; Si: 0.3-0.6%; Mn: 0.5-2.0%; Ni: 11.00~13.00%; Cr: 16.50~18.00%; Mo: 2.00-3.00%; N: 0.02-0.15%; and Cu: 0.01-0.30% the balance being Fe and unavoidable impurities; Cr, Mo, N, and Cu are subject to the following inequalities: Cr+3.3×Mo+16×N+10×Cu≧26.0% Meet the following.
[0011] In the tube of the present disclosure, in order to ensure the aluminum sulfate corrosion resistance of the tube, the aluminum sulfate corrosion resistance of the corrosion-resistant layer must first be ensured.
[0012] The operating conditions under which the corrosive aluminum sulfate medium is used in current water supply stations or water supply pipeline networks are as follows: the concentration of aluminum sulfate is less than 30% by weight, and the operating temperature is 0-40°C.
[0013] Based on the above operating conditions, the inventors optimized the chemical element composition of the corrosion-resistant layer of the tube, especially added a certain amount of Cu element, and designed a special corrosion resistance equivalence formula and requirements for controlling Cr, Mo, N, and Cu to satisfy the following inequality: Cr+3.3×Mo+16×N+10×Cu≧26.0%.
[0014] It should be noted that Cu can further improve the corrosion resistance of steel, especially in reducing media such as sulfate ions. The effect is more significant when Cu and Mo are added together. In general, the addition of copper will affect the thermomechanical performance of the material. However, for the tubes containing the composite material of the present disclosure, the proportion of the corrosion-resistant layer is relatively low, so the effect of the addition of copper on the overall thermomechanical performance is negligible.
[0015] In the present disclosure, the design principles of the chemical elements of the corrosion-resistant layer are as follows:
[0016] C: In the corrosion-resistant layer of the present disclosure, C is a strong austenite-forming element. To a certain extent, it replaces nickel, promotes austenite formation, stabilizes the austenite structure, and at the same time can improve the strength of stainless steel. However, the content of the C element should not be too high. If the carbon content is too high, carbon combines with chromium to form chromium-rich carbides at the grain boundaries, leading to intergranular corrosion. Therefore, in order to exert the beneficial effects of the C element, in the corrosion-resistant layer of the present disclosure, the mass percentage of the C element is controlled to satisfy 0 < C ≤ 0.08%.
[0017] Si: In the corrosion-resistant layer of the present disclosure, the main function of the Si element is to deoxidize during the smelting process. Therefore, it is generally necessary to add a certain amount of silicon. However, it should be noted that the content of the Si element should not be too high. If the silicon content is too high, the solubility of nitrogen will decrease. Therefore, in the corrosion-resistant layer of the present disclosure, the mass percentage of the Si element is controlled in the range of 0.3 - 0.6%.
[0018] Mn: In the corrosion-resistant layer of the present disclosure, the Mn element is an element that can strongly stabilize the austenite structure and increase the solubility of nitrogen in the steel. However, manganese has an adverse effect on the corrosion resistance of austenitic stainless steel. Therefore, in view of the beneficial effects and adverse effects of the Mn element, in the corrosion-resistant layer of the present disclosure, the mass percentage of the Mn element is controlled in the range of 0.5 - 2.0%, preferably 1.10 - 2.0%.
[0019] Ni: In the corrosion-resistant layer of the present disclosure, Ni is the most important element in the formation and stabilization of the austenite phase. By adding an appropriate amount of the Ni element, the formation of the austenite structure can be ensured in the steel at room temperature. However, nickel is expensive. It is not a good strategy to add excessive nickel to the steel to keep the cost relatively low. Therefore, in the corrosion-resistant layer of the present disclosure, the mass percentage of the Ni element is controlled in the range of 11.00 - 13.00%.
[0020] Cr: In the corrosion-resistant layer of the present disclosure, Cr ensures the rust-proof and corrosion-resistant properties of the steel. Generally, the minimum chromium content required for corrosion resistance is 10.5%. Since the chromium element significantly improves the corrosion resistance, in order to ensure good corrosion resistance, the chromium content in the disclosed steel is controlled to 16.50% or more. However, it should be noted that Cr is also the main element for producing ferrite. If the chromium content is too high, it is difficult to obtain an austenitic structure in the corrosion-resistant layer at room temperature. Therefore, in the corrosion-resistant layer of the present disclosure, the mass percentage of the Cr element is controlled in the range of 16.50-18.00%.
[0021] Mo: In the corrosion-resistant layer of the present disclosure, Mo is an important element for improving corrosion resistance. The mechanism by which Mo improves corrosion resistance is to stabilize the passive film and promote the enrichment of chromium element in the passive film. In addition, molybdenum acts synergistically with nitrogen to further improve pitting corrosion resistance. Therefore, the main function of molybdenum addition is to improve corrosion resistance. However, the content of Mo element should not be too high. If the content of molybdenum is too high, the cost of the alloy will increase. In order to ensure a relatively low cost, the mass percentage of Mo element is controlled in the range of 2.00-3.00% in the corrosion-resistant layer of the present disclosure.
[0022] N: In the corrosion-resistant layer of the present disclosure, N is a very powerful element in generating, stabilizing, and expanding the austenite region. The addition of an appropriate amount of N element can effectively improve the pitting corrosion resistance of stainless steel. However, if the nitrogen content in steel is too high, the risk of the formation of nitrogen-containing intermetallic phases increases, which increases the difficulties of smelting and thermal processing, making production difficult. Therefore, in the corrosion-resistant layer of the present disclosure, the mass percentage of N element is controlled in the range of 0.02-0.15%.
[0023] Cu: In the corrosion-resistant layer of the present disclosure, the addition of an appropriate amount of Cu element can improve the corrosion resistance of the material. In addition, the Cu element cooperates with molybdenum to stabilize the passive film and promote the enrichment of chromium in the passive film, thereby improving the pitting corrosion resistance. Therefore, in the corrosion-resistant layer of the present disclosure, the mass percentage of the Cu element is controlled in the range of 0.01-0.30%, preferably 0.12-0.30%, more preferably 0.12-0.22%.
[0024] Correspondingly, in the corrosion-resistant layer of the tube of the present disclosure, while controlling the mass percentage of each chemical element, the elements Cr, Mo, N, and Cu are also controlled to satisfy the following inequality: Cr+3.3×Mo+16×N+10×Cu≧26.0%, where each element in the formula is substituted with the mass percentage of the corresponding element. Through such control, the corrosion-resistant layer can further have excellent corrosion resistance in an aluminum sulfate environment.
[0025] Preferably, the unavoidable impurities in the corrosion-resistant layer include S≦0.030% and P≦0.045%.
[0026] In the corrosion-resistant layer of the tube of the present disclosure, both P and S are unavoidable impurities. In order to ensure the quality of the steel, the lower the content of impurities in the steel, the better, as long as conditions permit.
[0027] Preferably, the base layer comprises the following chemical elements in wt%: C: 0.01-0.20%; Si: 0.10-0.50%; Mn: 0.50-2.00%; Al: 0.02-0.04%; Ti: 0.005~0.014%; Nb: 0.005~0.020%; and N≦0.006% and the balance being Fe and unavoidable impurities.
[0028] Preferably, the base layer further comprises the following chemical elements: 0 <B≦0.0003%; 0 <Ni≦0.20%; 0 <Cr≦0.22%;および 0 <Mo≦0.12% Includes at least one of the following:
[0029] To be able to achieve high mechanical properties for the tube of the present disclosure, the inventors have also selected the chemical composition of the carbon steel of the base layer, which is selected to ensure both high strength and good workability.
[0030] Therefore, in the present disclosure, the design principles of the chemical elements in the carbon steel of the base layer are as follows:
[0031] C: In the base layer of the present disclosure, C is an element that can stabilize austenite and play the role of solid solution strengthening in steel, and significantly improve the strength of steel. However, the content of C element in steel should not be too high. If the content of C element in steel is too high, it is not only harmful to the welding performance and toughness of the material, but also tends to increase hard phase structures such as pearlite and martensite-austenite islands, which adversely affects the corrosion resistance of the steel. Therefore, in consideration of the balance between the strength and toughness of the steel plate and the requirements of the corrosion resistance of the carbon steel material, the mass percentage of C element in the steel of the base layer of the present disclosure is controlled in the range of 0.01-0.20%.
[0032] The mass percentage of the C element is controlled to 0.01-0.20%, which not only ensures that the steel plate has a predetermined hardness and strength when air-cooled after rolling, but also prevents the deterioration of the welding performance of the base layer steel.
[0033] Si: In the base layer of the present disclosure, the addition of Si element to steel can effectively improve the purity and deoxidation of steel. Si element can play the role of solid solution strengthening in steel. However, Si element does not contribute to the welding performance of the material. In the present disclosure, the silicon content of the carbon steel of the base layer is controlled to 0.50% or less so that the carbon steel of the base layer has good welding performance without affecting the corrosion resistance of the corrosion-resistant layer. Therefore, in the base layer of the present disclosure, the mass percentage of Si element is controlled to the range of 0.10-0.50%.
[0034] Mn: In the base layer of the present disclosure, the addition of an appropriate amount of Mn element to the steel can delay the transformation of pearlite, reduce the critical cooling rate, and improve the hardenability of the steel. In addition, the Mn element also has the effect of solid solution strengthening, and is the main solid solution strengthening element in steel. However, the amount of Mn element added should not be too much. If the content of Mn element in the steel is too high, segregation bands and martensite structures that adversely affect the toughness of the steel are likely to be formed, and the appearance of segregation bands also leads to a decrease in the corrosion resistance of the steel. In general, the manganese content in the low carbon microalloy steel does not exceed 2.00% so that the Mn element contained in the carbon steel of the base layer does not adversely affect the corrosion resistant layer. Therefore, in the base layer of the present disclosure, the mass percentage of the Mn element is controlled in the range of 0.50 to 2.00%.
[0035] Al: In the base layer of the present disclosure, Al is a strong deoxidizing element. Al is added so that the oxygen content in the steel is as low as possible. The residual Al after deoxidation combines with the N element in the steel to form AlN precipitates, which can improve the strength of the steel and refine the primary grain size of austenite in the steel during heat treatment. However, if the Al content is too high, it can easily lead to the generation of alumina inclusions. Therefore, in the base layer of the present disclosure, the mass percentage of the Al element is controlled in the range of 0.02-0.04%.
[0036] Ti: In the base layer of the present disclosure, Ti is a strong carbide-forming element. The addition of a small amount of Ti to steel is beneficial to the fixation of N in the steel. The TiN generated by the combination of Ti and N can prevent the austenite grains in the base layer from growing excessively when the base layer slab is heated, and refine the primary grain size of the austenite. In addition, Ti can also combine with carbon and sulfur in the steel to generate compounds such as TiC, TiS, Ti4C2S2, and can exist in the form of inclusions and second phase particles. In addition, these carbonitride precipitates of Ti can also prevent grain growth in the heat-affected zone during welding and improve the welding performance. However, if the Ti content is too high, it will lead to a large amount of carbides such as titanium carbide and their segregation and enrichment, which will affect the mechanical properties of the material. Therefore, in the base layer of the present disclosure, the mass percentage of Ti element is controlled in the range of 0.005-0.014%.
[0037] Nb: In the base layer of the present disclosure, Nb is a strong carbide-forming element. The main purpose of adding a small amount of niobium to the carbon steel of the base layer is to increase the recrystallization temperature to match the high final rolling temperature of the clad plate formed by combining the base layer slab and the corrosion-resistant layer slab in the subsequent rolling process, so that the grains in the recrystallized and non-recrystallized regions of the base layer are refined after rolling, which is beneficial to improving the low-temperature impact toughness of the base layer. However, too high a Nb content will lead to the formation of large-sized Nb-rich precipitates, which will reduce the plastic toughness of the material. Therefore, in the base layer of the present disclosure, the mass percentage of Nb element is controlled in the range of 0.005-0.020%.
[0038] N: In the base layer of the present disclosure, N element can form second phase particles together with titanium and aluminum to refine the crystal grains and improve strength. However, if the mass percentage of N element is too high, too much TiN is generated, and the particles become too coarse, which affects the plasticity of the carbon steel plate of the base layer of the composite of the present disclosure. Therefore, in the base layer of the present disclosure, the mass percentage of N element is controlled to N: 0.006% or less.
[0039] B: In the present disclosure, B can greatly improve the hardenability of steel. When air cooling is carried out after rolling to manufacture a high corrosion-resistant clad plate (corrosion-resistant layer slab + base layer slab), it is necessary to obtain as much ferrite + pearlite structure as possible to suppress the formation of bainite. However, if the B content is too high, it will cause segregation and tend to form compounds with oxygen and nitrogen, and as a result, the corresponding purpose cannot be achieved. Therefore, in the present disclosure, it is necessary to control the addition amount of B element in the base layer so that 0 < B ≤ 0.0003% is satisfied.
[0040] Ni: In the present disclosure, Ni is an element that stabilizes austenite and has a certain effect on improving the strength of steel. In addition, by adding an appropriate amount of Ni to steel, especially to quenched and tempered steel, the low-temperature impact toughness of steel can be significantly improved. However, if the Ni content is too high, it will increase the carbon equivalent and affect the welding performance. Also, Ni is a rare metal that causes waste of resources and increase in cost. Therefore, in the base layer of the present disclosure, an appropriate amount of Ni can be added, and the addition amount of Ni element is controlled to satisfy 0 < Ni ≤ 0.20%.
[0041] Cr: In the present disclosure, the Cr element has a lower segregation tendency than Mn. When the Mn content in the carbon steel of the base layer is high and obvious segregation bands and banded structures exist in the steel, the Mn content can be appropriately reduced, and the insufficient part can be replaced with Cr. Second, adding an appropriate amount of Cr element to the carbon steel of the base layer also helps to suppress the diffusion of Cr in the corrosion-resistant layer into the base layer. However, if the Cr content is too high, it will affect the phase transition temperature of the base material and the mechanical properties of the base material. Therefore, in the base layer of the present disclosure, a Cr element with a content of 0 < Cr ≤ 0.22% can be added.
[0042] Mo: In the present disclosure, the Mo element can significantly refine crystal grains and improve the strength and toughness of steel. In addition, Mo can also reduce the temper brittleness of steel, can precipitate very fine carbides during tempering, and the steel in the base layer is significantly strengthened. In addition, the addition of the Mo element is also beneficial for suppressing the self-temper brittleness that easily occurs in the steel plate during air cooling. However, if the Mo content is too high, it will increase the carbon equivalent, affect the welding performance, and lead to waste of resources and increase in cost. Therefore, in the base layer of the present disclosure, an appropriate amount of Mo can be added, and the addition amount of the Mo element is controlled to satisfy 0 < Mo ≤ 0.12%.
[0043] Preferably, the single-layer corrosion-resistant layer has a thickness that occupies 0.5 to 10% of the total thickness of the pipe, and the base layer has the following chemical elements in wt%: C: 0.01 to 0.18%; Si: 0.10 to 0.30%; Mn: 0.50 to 1.50%; Al: 0.02 to 0.03%; Ti: 0.005 to 0.014%; Nb: 0.005 to 0.015%; and N ≤ 0.006% including, with the balance being Fe and inevitable impurities.
[0044] Preferably, the inevitable impurities in the base layer include S ≤ 0.010% and P ≤ 0.015%.
[0045] In the above technical solution of the present disclosure, P and S are inevitable impurities in the base layer. S in steel will combine with Mn to form manganese sulfide, which is a plastic inclusion, and this is particularly harmful to the transverse plasticity and toughness of steel. Therefore, the content of the S element in the base layer should be as low as possible. In addition, P is also a harmful element in steel and may severely damage the plasticity and toughness of the steel plate.
[0046] Therefore, in the present disclosure, both S and P are inevitable impurities, and their contents should be as low as possible. Considering the actual steelmaking level of the steel mill, the S and P elements in the base layer of the present disclosure are controlled to satisfy S≦0.010% and P≦0.015%.
[0047] Preferably, the single corrosion-resistant layer has a thickness that is 0.5-50%, more preferably 2.5-28.6%, of the total thickness of the tube. In other words, if the tube has a corrosion-resistant layer on both the inner and outer surfaces, the thickness of each corrosion-resistant layer is 0.5-50% of the total thickness of the tube. If the tube has only a corrosion-resistant layer on the inner surface, the thickness of the corrosion-resistant layer is 0.5-50% of the total thickness of the tube.
[0048] In the present disclosure, the selection of the thickness of the corrosion-resistant layer plays a vital role in obtaining good corrosion resistance, mechanical properties, and formability of the tube of the present disclosure according to the operating conditions. If the corrosion-resistant layer is too thick, it will affect the mechanical properties and production cost of the material. If the corrosion-resistant layer is too thin, it will reduce the corrosion resistance and service life of the material. Therefore, in the present disclosure, it is preferable to control the thickness of the single-layer corrosion-resistant layer to 0.5-50% of the total thickness of the tube, more preferably 2.5-28.6%.
[0049] Preferably, the single corrosion resistant layer has a thickness that accounts for 2.5 to 20% of the total thickness of the pipe.
[0050] Preferably, the base layer has a ferrite+pearlite or ferrite+pearlite+bainite microstructure and the corrosion resistant layer has an austenite microstructure.
[0051] Preferably, there is a diffusion or transition layer between the corrosion resistant layer and the base layer, the diffusion or transition layer having a thickness of about 50 to 120 μm.
[0052] Preferably, the pipe has a yield strength of 426 MPa or greater, a tensile strength of 580 MPa or greater, an elongation of 31% or greater, and a uniform corrosion rate (i.e., average corrosion rate) of 0.05 mm / year or less in an environment having a temperature of 40° C. or less and an aluminum sulfate concentration of 30 wt % or less.
[0053] Therefore, another object of the present disclosure is to provide a method for manufacturing the above-mentioned tube, which is simple, feasible and can be effectively used to prepare the above-mentioned tube.
[0054] In order to achieve the above object, the present invention provides a method for manufacturing the above-mentioned tube, comprising the following steps: (1) preparing a corrosion-resistant layer slab and a base layer slab; (2) combining the corrosion-resistant layer slab with the base layer slab to obtain a clad slab, in which the single-layer corrosion-resistant layer has a thickness that preferably accounts for 0.5-50%, more preferably 2.5-28.6%, of the total thickness of the clad slab (the ratio of the thickness of the single-layer corrosion-resistant layer to the total thickness of the tube for the finished tube is essentially the same as the thickness ratio described in this step); (3) Heating and rolling step: heating the clad slab at a temperature of 1150-1200°C, and then carrying out multi-pass rolling, in which the total reduction is 90% or more, and the final rolling is carried out at a temperature of 920°C or more; (4) coiling step: after water cooling, coiling is carried out at a temperature of 500 to 620°C to obtain a hot-rolled coil; (5) performing a surface treatment on the hot rolled coil; and (6) Pipe manufacturing process The present invention provides a method comprising:
[0055] In the above-mentioned manufacturing method of the present disclosure, the smelting and casting process can be designed according to the chemical composition to prepare a corrosion-resistant layer slab and a base layer slab, which can then be combined to obtain a clad plate (corrosion-resistant layer plate + base layer plate) with high corrosion resistance. The obtained clad plate with high corrosion resistance can be further heated, rolled and coiled to obtain a hot-rolled coil with a clad interlayer structure. The tube of the present disclosure can be obtained by subjecting the hot-rolled coil to surface treatment and then tube production.
[0056] In this disclosure, the inventors have optimized the design of the heating and rolling process in step (3) to form a transition layer structure of a predetermined thickness between the corrosion-resistant layer and the base layer through heating, rolling and other processes, so as to achieve a perfect metallurgical bond between the corrosion-resistant layer and the base layer, thereby ensuring the resistance to aluminum sulfate corrosion and mechanical properties while improving the applicability and economics of the material, thereby resolving the inherent weaknesses of the 300 series stainless steel or carbon steel currently used in water stations in environments containing aluminum sulfate corrosive media.
[0057] In step (2) of the manufacturing method of the present disclosure, the prepared corrosion-resistant layer slab and base layer slab can be pre-treated, the adjacent flat surfaces of each slab can be welded and sealed at the edges, and a vacuum treatment can be performed on the joint surfaces after welding and sealing to complete the assembly.
[0058] Correspondingly, in step (5), pickling or mechanical descaling can be used for surface treatment of the hot rolled coil. In addition, in the tube manufacturing process of step (6), traditional spiral welding or straight seam welding can be used for forming and welding, and the welding method can be selected from submerged arc welding, metal gas arc welding, tungsten inert gas welding, plasma arc welding, welding rod arc welding, high frequency welding, and laser welding.
[0059] Preferably, in step (3), the final rolling is carried out at a temperature of 920 to 1000°C.
[0060] Preferably, the method further comprises a preheating step between step (2) and step (3), and the preheating is carried out at a temperature of 1100-1250°C.
[0061] In the manufacturing method of the present disclosure, whether to carry out a preheating process between step (2) and step (3) can also be determined according to the performance requirements of the finished product. In the preheating process, the clad slab obtained by combining the slabs can be heated at a temperature of 1100-1250°C, so that a uniform austenitic structure is obtained in the corrosion-resistant layer on the surface of the clad slab, and the carbides that may exist beforehand are completely dissolved, while the compounds of alloying elements such as niobium and titanium in the carbon steel are completely or partially dissolved, and the elements in the corrosion-resistant layer and the carbon steel of the base layer diffuse at the interface to form a stable transition layer, which is then slowly cooled to room temperature.
[0062] Preferably, the method further comprises cold rolling and annealing between steps (5) and (6). Preferably, the annealing is carried out at a temperature of 900-1000°C.
[0063] In the manufacturing method of the present disclosure, in practical use, if the target product before tube production is a cold-rolled coil rather than a hot-rolled coil, a cold rolling and annealing step may be further added between step (5) and step (6) to cold-roll the coil to a target thickness and then perform annealing.
[0064] As shown above, in this disclosure, the inventors have designed the composition of the corrosion-resistant layer and the base layer and the ratio of both layers. A corrosion-resistant layer resistant to aluminum sulfate corrosion is formed on the surface of the carbon steel plate of the base layer through the rolling process, thereby obtaining a plate or strip resistant to aluminum sulfate corrosion and having good mechanical properties and high economic efficiency. The plate or strip can then be processed into a pipe and effectively used in the pipeline and equipment of the water supply station in an environment containing aluminum sulfate corrosive medium.
[0065] It should be noted that the challenges in designing this disclosure include the following. 1) The design of the composition of the corrosion-resistant layer and the base layer must meet the comprehensive performance of the material. The composition of the corrosion-resistant layer must be designed based on the resistance to aluminum sulfate corrosion to meet the requirements of corrosion resistance under operating conditions. In addition to meeting the mechanical property requirements, the composition design of the carbon steel of the base layer must take into account the following: when the carbon content in the transition layer between the two layers is high, there is a shortage of stabilizing elements, and an obvious decarburization layer occurs on the carbon steel side of the interface joint, resulting in a non-uniform carbon steel structure of the base material, which is prone to surface defects after processing and difficult to meet the mechanical properties. 2) Due to the difference in the ratio and material properties of the corrosion-resistant layer metal and the base layer metal, it is difficult to control the heating process, rolling process, and heat treatment process. For example, the temperature during heating will be uneven, causing deformation and swelling, and as a result, it cannot be bonded with the base layer. For example, it will tend to separate from the substrate and crack during the rolling process, and it will be difficult to ensure the uniformity of the thickness. 3) For pipes and equipment such as aluminum sulfate mixing tanks, concentrated tanks, connecting pipes for tank bodies, and pipes for adding aluminum sulfate used in water supply stations in environments containing aluminum sulfate corrosive media, if the initial cladding is not completed and the bonding quality is poor, the continuity and uniformity of the corrosion-resistant layer of the finished product cannot be guaranteed after the subsequent pickling, pipe manufacturing and forming, welding and other processes, which will bring a very large hidden danger to the applicability, safety and durability of the equipment and pipes.
[0066] In the present disclosure, the inventors have succeeded in overcoming the above difficulties through rational design, whereby the tubes of the present disclosure are prepared and obtained.
[0067] Compared with the prior art, the tube and its manufacturing method of the present disclosure have the following advantages and beneficial effects:
[0068] In this disclosure, when the inventors consider the operating conditions of the current pipelines and equipment in the water supply station in the environment containing aluminum sulfate corrosive medium, and design the composition of the corrosion-resistant layer and the base layer and the ratio of both layers, the corrosion-resistant layer and the base layer are bonded into a slab and subjected to a suitable process such as heating, rolling, coiling, and pipe manufacturing to obtain a pipe that is resistant to aluminum sulfate corrosion and has good mechanical properties and high economic efficiency. The pipe has a yield strength of 426 MPa or more, a tensile strength of 580 MPa or more, an elongation of 31% or more, and a uniform corrosion rate (i.e., average corrosion rate) of 0.05 mm / year or less in an environment where the temperature is 40°C or less and the aluminum sulfate concentration is 30 wt% or less.
[0069] In the present disclosure, a transition layer structure of a predetermined thickness is formed between the corrosion-resistant layer and the base layer through processes such as heating and rolling, so that a perfect metallurgical bond between the corrosion-resistant layer and the base layer can be achieved, thereby ensuring the resistance to aluminum sulfate corrosion and mechanical properties while improving the applicability and economics of the material.
[0070] The pipes manufactured using the above designed composition and process control method can solve the inherent weaknesses of 300 series stainless steel or carbon steel used in water supply stations in environments containing aluminum sulfate corrosive media. The pipes can be effectively used in pipelines and equipment such as aluminum sulfate mixing tanks, concentrated tanks, connecting pipes for tank bodies, and pipes for adding aluminum sulfate, which are used in water supply stations in environments containing aluminum sulfate media. The pipes can meet the requirements of these pipelines and equipment for resistance to aluminum sulfate corrosion and mechanical properties, greatly improving the applicability, safety, and durability of these pipelines and equipment while avoiding secondary pollution of water quality, and have great economic and social benefits.
[0071] Compared with the 300 series stainless steel pipes currently used in aluminum sulfate mixing tanks, thickening tanks, connecting pipes for tank bodies, and pipes for adding aluminum sulfate in water supply plants, the pipes of the present disclosure have higher strength and better corrosion resistance, are simpler to weld and machine, and are more economical.Compared with the carbon steel pipes, the steel plate or strip for the pipes disclosed in the present disclosure can omit the process of corrosion-resistant coating on the pipes, and has corrosion resistance and durability that are difficult to achieve with carbon steel pipes, and is more energy-saving, environmentally friendly, and maintenance-free. [Brief description of the drawings]
[0072] [Figure 1] FIG. 2 is a schematic diagram of a tube interlayer structure according to one embodiment of the present disclosure. [Diagram 2] FIG. 13 is a schematic diagram of an interlayer structure of a tube according to another embodiment of the present disclosure. [Diagram 3] 4 is a photograph of the microstructure of the bonding interface between the base layer and the corrosion-resistant layer of the tube of Example 4. [Figure 4] 1 is a photograph of the microstructure of the base layer of the tube of Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0073] The tube and its manufacturing method of the present disclosure will be further illustrated and explained below with reference to specific examples. However, the illustrations and explanations do not unduly limit the technical solutions of the present disclosure.
[0074] Examples 1 to 8 Table 1 shows the mass percentage of each chemical element in the corrosion-resistant layer of the pipes of Examples 1-8.
[0075] [Table 1]
[0076] Table 2 shows the mass percentage of each chemical element in the base layer of the pipes of Examples 1-8.
[0077] [Table 2]
[0078] The following steps were used to manufacture all of the tubes of Examples 1-8 of the present disclosure. (1) According to the chemical compositions shown in Tables 1 and 2, smelting and casting were carried out to prepare corrosion-resistant layer slabs and base layer slabs, respectively. (2) Combining the corrosion-resistant layer slab and the base layer slab to obtain a clad slab: controlling the single-layer corrosion-resistant layer to have a thickness accounting for 0.5-50% of the total thickness of the clad slab (the ratio of the thickness of the single-layer corrosion-resistant layer to the total thickness of the tube for the finished tube was basically the same as the thickness ratio described in this step); pre-treating the corrosion-resistant layer slab and the base layer slab; welding and sealing the edges of the adjacent planes of each slab; performing vacuum treatment on the joint surfaces after welding and sealing; after combining the slabs, determining whether to carry out a pre-heating process according to the performance requirements of the finished product; if pre-heating, pre-heating the slab at a pre-heating temperature of 1100-1250°C. (3) Heating and rolling step: the clad slab was heated at a temperature of 1150-1200°C, and then multi-pass rolling was carried out within the range of the recrystallization temperature and non-recrystallization temperature of austenite in the corrosion-resistant layer slab and the base layer slab, with the total rolling reduction being 90% or more, and the final rolling temperature being 920°C or more, preferably in the range of 920-1000°C. (4) Coiling step: After water cooling, coiling was carried out at a temperature of 500 to 620°C to obtain a hot-rolled coil. (5) Surface treatment is carried out on the hot rolled coil by pickling or mechanical methods to remove phosphorus. If the target product is a cold rolled coil, cold rolling and annealing processes are further carried out. After cold rolling to the target thickness, annealing is carried out at an annealing temperature of 900-1000°C. (6) Tube manufacturing step: Spiral welding or straight seam welding was used for forming and welding. The welding method can be selected from various methods such as submerged arc welding, metal gas arc welding, tungsten inert gas welding, plasma arc welding, welding rod arc welding, high frequency welding, and laser welding for tube manufacturing.
[0079] It should be noted that in the present disclosure, the tubes of Examples 1 to 8 of the present disclosure were all produced using the above process steps of step (1) to step (6), and their chemical compositions and related process parameters all met the designed specification control requirements of the present disclosure.
[0080] Table 3 shows the specific process parameters for the steps of the above manufacturing method for the tubes of Examples 1-8.
[0081] [Table 3]
[0082] It should be noted that according to the process parameters shown in Table 3 above, for Example 1 and Example 3, after the surface treatment of the hot-rolled coil in step (5), cold rolling and annealing were further carried out to obtain cold-rolled sheets, while for Example 2 and Examples 4 to 8, hot-rolled sheets were obtained by step (5).
[0083] Correspondingly, for Examples 1 to 8, the plates prepared in step (5) were further used to prepare corresponding tubes in the tube manufacturing process of step (6).
[0084] The finished tubes of Examples 1 to 8 produced by the above process were sampled to further observe the microstructures of the tube samples of Examples 1 to 8. After observing the microstructure of the tubes of each Example, the mechanical properties of the tube samples of Examples 1 to 8 were tested. The test results obtained are shown in Table 4 below.
[0085] The test methods for relevant mechanical properties are as follows: The tests were conducted according to GB / T 6396-2008 “Clad steel plates-Mechanical and technological test” to determine the yield strength, tensile strength and elongation of the tube samples of Examples 1-8.
[0086] Table 4 shows the microstructure and mechanical property test results for the tubes of Examples 1-8.
[0087] [Table 4]
[0088] Correspondingly, in order to verify the aluminum sulfate corrosion resistance of the tubes of Examples 1 to 8 prepared according to the present disclosure, the tubes of Examples 1 to 8 were sampled again, and aluminum sulfate corrosion resistance tests were carried out on the obtained tube samples of Examples 1 to 8. The test results are shown in Table 5 below.
[0089] Aluminum sulfate corrosion resistance test: The samples of Examples 1 to 8 were suspended in an aluminum sulfate solution (temperature ≦40°C and aluminum sulfate concentration ≦30wt%). After 3 months, they were taken out and the surface state of the corrosion-resistant layer was observed. The weight loss at the start of corrosion was measured to confirm the presence or absence of corrosion phenomenon, and the annual corrosion rate of each Example was calculated to obtain the aluminum sulfate corrosion resistance of the pipe samples of Examples 1 to 8.
[0090] Table 5 shows the aluminum sulfate corrosion resistance test results for the tubes of Examples 1 to 8.
[0091] [Table 5]
[0092] Considering the above Tables 4 and 5 together, it can be seen that in the present disclosure, the tubes of Examples 1-8 exhibited excellent mechanical properties with yield strengths ranging from 426 to 508 MPa, tensile strengths ranging from 580 to 650 MPa, and elongations ranging from 31.0% to 40.5%. At the same time, Examples 1-8 also exhibited good aluminum sulfate corrosion resistance with aluminum sulfate annual corrosion rates of 0.05 mm / year or less under the test environment.
[0093] From the above examples, it can be seen that by adopting appropriate materials, composition design, rolling and heat treatment processes in the present disclosure and combining with the pipe manufacturing process, a pipe with good corrosion resistance and mechanical properties can be obtained, thereby solving the inherent weaknesses of 300 series stainless steel or carbon steel used in water supply stations in environments containing aluminum sulfate corrosive media, and meeting the requirements of pipelines and equipment used in water supply stations in environments containing aluminum sulfate corrosive media, showing great economic and social benefits.
[0094] FIG. 1 is a schematic diagram of an interlayer structure of a tube according to one embodiment of the present disclosure.
[0095] As shown in FIG. 1, in this embodiment, the tube of the present disclosure includes two corrosion resistant layers located on the inner and outer surfaces of the tube, and a base layer located therebetween.
[0096] FIG. 2 is a schematic diagram of an interlayer structure of a tube according to another embodiment of the present disclosure.
[0097] As shown in FIG. 2, in this embodiment, the tube of the present disclosure includes a corrosion resistant layer located on the inner surface of the tube and a base layer located on the outer surface of the tube.
[0098] FIG. 3 is a photograph of the microstructure of the bond interface between the base layer and the corrosion resistant layer of the tube of Example 4.
[0099] FIG. 4 is a photograph of the microstructure of the base layer of the tube of Example 4.
[0100] As shown in Figures 3 and 4, in Example 4, the tube had a total thickness of 12 mm and the single layer corrosion resistant layer had a thickness of 2 mm.
[0101] In Example 4, it was observed that the base layer of the tube had a ferrite+pearlite microstructure, and the corrosion-resistant layer had an austenite microstructure. Correspondingly, in the present disclosure, elements in the corrosion-resistant layer and the base layer diffused at the bonding interface to form a stable diffusion layer (i.e., transition layer), with the diffusion distance (i.e., thickness of the transition layer) being about 50 μm to 120 μm.
[0102] It should be noted that the prior art part within the protection scope of the present disclosure is not limited to the embodiments described in the present disclosure. All prior art that is not inconsistent with the solution of the present disclosure, including but not limited to prior patent documents, prior publications, prior public use, etc., is included in the protection scope of the present disclosure.
[0103] In addition, the combinations of various technical features in the present disclosure are not limited to the combinations described in the claims or the combinations described in the specific examples. All technical features described in the present disclosure can be combined freely or in any way as long as they are not mutually inconsistent.
[0104] It should also be noted that the above-mentioned embodiments are merely specific examples of the present disclosure. Obviously, the present disclosure is not limited to the above-mentioned embodiments. All similar modifications or variations that can be directly derived or easily conceived by those skilled in the art from the content of the present disclosure should be included within the protection scope of the present disclosure.
Claims
1. A tube having a corrosion resistant layer and a base layer through its thickness, said corrosion resistant layer being located at least on an inner wall of said tube, said corrosion resistant layer further comprising the following chemical elements in wt % in addition to Fe and inevitable impurities: 0<C≦0.08%; Si: 0.3-0.6%; Mn: 0.5-2.0%; Ni: 11.00-13.00%; Cr: 16.50-18.00%; Mo: 2.00-3.00%; N: 0.02 to 0.15%; and Cu: 0.01 to 0.3%, preferably Cu: 0.12 to 0.3%, more preferably Cu: 0.12 to 0.22% wherein Cr, Mo, N, and Cu satisfy the following inequalities: Cr+3.3×Mo+16×N+10×Cu≧26.0% Fill the tube.
2. The corrosion resistant layer comprises the following chemical elements in wt %: 0<C≦0.08%; Si: 0.3-0.6%; Mn: 0.5-2.0%; Ni: 11.00-13.00%; Cr: 16.50-18.00%; Mo: 2.00-3.00%; N: 0.02-0.15%; Cu: 0.01 to 0.3%, preferably Cu: 0.12 to 0.3%, more preferably Cu: 0.12 to 0.22% The balance being Fe and unavoidable impurities; Cr, Mo, N, and Cu satisfy the following inequality: Cr+3.3×Mo+16×N+10×Cu≧26.0% The tube of claim 1 ,
3. 3. The tube according to claim 1 or 2, wherein the inevitable impurities in the corrosion resistant layer include S≦0.030% and P≦0.045%.
4. The base layer comprises the following chemical elements in wt %: C: 0.01-0.20%; Si: 0.10-0.50%; Mn: 0.50-2.00%; Al: 0.02-0.04%; Ti: 0.005-0.014%; Nb: 0.005-0.020%; and N≦0.006% and the balance being Fe and inevitable impurities.
5. The single layer corrosion resistant layer has a thickness of 0.5-10% of the total thickness of the tube, and the base layer contains the following chemical elements in wt %: C: 0.01-0.18%; Si: 0.10-0.30%; Mn: 0.50-1.50%; Al: 0.02-0.03%; Ti: 0.005-0.014%; Nb: 0.005-0.015%; and N≦0.006% and the balance being Fe and incidental impurities.
6. The base layer further comprises the following chemical elements: 0<B≦0.0003%; 0<Ni≦0.20%; 0<Cr≦0.22%; and 0<Mo≦0.12% The tube of claim 4 , comprising at least one of:
7. 5. The tube of claim 4, wherein the inevitable impurities in the base layer include S≦0.010% and P≦0.015%.
8. 3. A tube according to claim 1 or 2, wherein the single anti-corrosion layer has a thickness which accounts for 0.5-50%, preferably 2.5-28.6%, of the total thickness of said tube.
9. 9. The tube of claim 8, wherein the single layer corrosion resistant layer has a thickness that is between 2.5 and 20% of the total thickness of the tube.
10. 3. The tube of claim 1 or 2, wherein the base layer has a ferrite+pearlite or ferrite+pearlite+bainite microstructure and the corrosion resistant layer has an austenite microstructure.
11. 3. The pipe of claim 1 or 2, having a yield strength of 426 MPa or more, a tensile strength of 580 MPa or more, an elongation of 31% or more, and an average corrosion rate of 0.05 mm / year or less in an environment having a temperature of 40° C. or less and an aluminum sulfate concentration of 30 wt % or less.
12. A method for manufacturing a tube according to any one of claims 1 to 11, comprising the steps of: (1) preparing a corrosion-resistant layer slab and a base layer slab; (2) combining the corrosion-resistant layer slab with the base layer slab to obtain a clad slab, wherein the single-layer corrosion-resistant layer has a thickness that preferably accounts for 0.5-50%, more preferably 2.5-20%, of the total thickness of the clad slab; (3) Heating and rolling step: heating the clad slab at a temperature of 1150-1200°C, and then carrying out multi-pass rolling, in which the total reduction is 90% or more, and the final rolling is carried out at a temperature of 920°C or more; (4) coiling step: after water cooling, coiling is carried out at a temperature of 500 to 620°C to obtain a hot-rolled coil; (5) performing a surface treatment on the hot rolled coil; and (6) Pipe manufacturing step The method includes:
13. The method according to claim 12, wherein in step (3), the final rolling is carried out at a temperature of 920 to 1000°C.
14. 13. The method of claim 12, further comprising a step of preheating between steps (2) and (3), wherein said preheating is performed at a temperature of 1100-1250°C.
15. The method according to claim 12, further comprising cold rolling and annealing between steps (5) and (6), said annealing being preferably carried out at a temperature of 900-1000°C.
Citation Information
Patent Citations
TMCP type marine austenitic stainless steel composite plate and preparation method thereof
CN108943911A
High-corrosion-resistance strip steel and manufacturing method thereof
CN113106327A
Manufacture of wear resistant steel pipe
JP1993279738A
Stainless-clad steel excellent in chemical resistance
JP2012149309A
Super austenitic stainless steel rolled composite steel plate and its manufacturing method
JP2020509159A